Avaliação dos erros matemáticos do aluno em prova do vestibular e durante o curso de graduação - Alaor Leao Rocha (2005)
This study aims to research if the mathematics erros mistakes found on the entrance examinations maintain on the eight periods of Matematics graduation. It raised the followings questions: to what extent mistakes made by students over the entrance examinations had effect over learning of the licensed ones? Do the diagnosed mistakes over the entrance examinations reappear during the graduating process? When? How ? Does the University do any kind of analytical work over the mistakes? It was taken the entrance examination of 2004 and had application on the end of 2°, 4º, 6º and 8º period of the curs to search the mistakes incident on the 12 questions of the concerning examinations, have gather on the quantitative facts the opinion of teachers and students about over the mistake just moment of answer the questionnaire. Concluded that there was a significant growth between the entrance examination and the examination on the 2º periods, but the growth between another periods was on this side of the desirable. Wait that this dissertation can contribute for an improvement formations quality of students of the mathematic curs. So as of University FAREU, as other, she is subsidiarying a methodology revision of her curriculum.